2012
DOI: 10.1039/c1nr11313e
|View full text |Cite
|
Sign up to set email alerts
|

Optical materials based on molecular nanoparticles

Abstract: A major part of contemporary nanomaterials research is focused on metal and semiconductor nanoparticles, constituted of extended lattices of atoms or ions. Molecular nanoparticles assembled from small molecules through non-covalent interactions are relatively less explored but equally fascinating materials. Their unique and versatile characteristics have attracted considerable attention in recent years, establishing their identity and status as a novel class of nanomaterials. Optical characteristics of molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 203 publications
0
85
0
Order By: Relevance
“…These CDs also show low cytotoxicity and excellent cellular imaging capability. The facile preparation and unique optical features make these CDs potentially useful in numerous applications such as lightemitting diodes, full-color displays, and multiplexed (UC)PL bioimaging.Multicolor photoluminescent (PL) materials, which can be excited by a single wavelength, continue to fascinate mankind because of their potential applications in sensing, bioimaging, light-emitting diodes, full-color displays, and optoelectronic devices.[1] Many multicolor emissive materials have been developed in the past decades, and include semiconductor quantum dots (QDs), [2] rare-earth based nanoparticles, [3] polymer dots, [4] molecular nanomaterials, [5] and organic fluorescent dyes, [6] but the potentially high toxicity, lowemission quantum yields (QYs), potential for photobleaching, poor water solubility, and complicated preparation procedures have hampered their practical applications. [2][3][4][5][6] Recently, carbon-based fluorescent nanomaterials, such as carbon dots (CDs), have attracted much attention because of their unique optical and low/nontoxic features.…”
mentioning
confidence: 99%
“…These CDs also show low cytotoxicity and excellent cellular imaging capability. The facile preparation and unique optical features make these CDs potentially useful in numerous applications such as lightemitting diodes, full-color displays, and multiplexed (UC)PL bioimaging.Multicolor photoluminescent (PL) materials, which can be excited by a single wavelength, continue to fascinate mankind because of their potential applications in sensing, bioimaging, light-emitting diodes, full-color displays, and optoelectronic devices.[1] Many multicolor emissive materials have been developed in the past decades, and include semiconductor quantum dots (QDs), [2] rare-earth based nanoparticles, [3] polymer dots, [4] molecular nanomaterials, [5] and organic fluorescent dyes, [6] but the potentially high toxicity, lowemission quantum yields (QYs), potential for photobleaching, poor water solubility, and complicated preparation procedures have hampered their practical applications. [2][3][4][5][6] Recently, carbon-based fluorescent nanomaterials, such as carbon dots (CDs), have attracted much attention because of their unique optical and low/nontoxic features.…”
mentioning
confidence: 99%
“…Hence, organic nanocrystals (ONCs), whose solubility and morphology are difficult to control, have not been employed in polymer/nanohybrids. Aromatic ONCs can be robust and exhibit useful photonic properties, [11][12][13][14][15][16] yet their fabrication is based mostly on empirical methods. 17 Addressing this challenge, we have recently demonstrated that rational design based on hydrophobicity tuning can be applied to control structure and morphology, resulting in soluble and tunable ONCs.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of the nanodevices are fabricated from inorganic nanowires and carbon nanotubes, whereas only a few such photoconductive one dimensional (1D) nanostructures have been reported on organic materials [1][2][3][4][5][6][7]. They have various advantages over their inorganic counterparts including chemically tunable electronic and optical properties and conformal flexibility and adaptability.…”
Section: Introductionmentioning
confidence: 99%